Antimicrobial resistance in equine reproduction - Malaluang, P.; Wilén, E.; Lindahl, Johanna F.; Hansson, I.; Morrell, J.M. (MDPI, 2021)
Bacteria develop resistance to antibiotics following low-level "background" exposure to antimicrobial agents as well as from exposure at therapeutic levels during treatment for bacterial infections. In this review, we look specifically at antimicrobial resistance (AMR) in the equine reproductive tract and its possible origin, focusing particularly on antibiotics in semen extenders used in preparing semen doses for artificial insemination. Our review of the literature indicated that AMR in the equine uterus and vagina were reported worldwide in the last 20 years, in locations as diverse as Europe, India, and the United States. Bacteria colonizing the mucosa of the reproductive tract are transferred to semen during collection; further contamination of the semen may occur during processing, despite strict attention to hygiene at critical control points. These bacteria compete with spermatozoa for nutrients in the semen extender, producing metabolic byproducts and toxins that have a detrimental effect on sperm quality. Potential pathogens such as Klebsiella pneumoniae, Escherichia coli, and Pseudomonas aeruginosa may occasionally cause fertility issues in inseminated mares. Antibiotics are added during semen processing, according to legislation, to impede the growth of these microorganisms but may have a detrimental effect on sperm quality, depending on the antimicrobial agent and concentration used. However, this addition of antibiotics is counter to current recommendations on the prudent use of antibiotics, which recommend that antibiotics should be used only for therapeutic purposes and after establishing bacterial sensitivity. There is some evidence of resistance among bacteria found in semen samples. Potential alternatives to the addition of antibiotics are considered, especially physical removal separation of spermatozoa from bacteria. Suggestions for further research with colloid centrifugation are provided.